Recent Bank Mergers - Alhadeff, Charlotte P.; Alhadeff, David A. (Quarterly Journal of Economics, 1955)
I. Introduction, 503. — II. Factors behind the recent mergers, 504. — III. Government regulation of bank mergers, 519. — IV. Effects of mergers upon banking markets, 524. — V. Conclusions, 531.